ABDOMINAL PREGNANCY A CASE REPORT - Farooq, Shafaq (Journal of Postgraduate Medical Institute, 2011)
Abdominal pregnancy in the third trimester is rare; the subsequent delivery of a viable full term fetus is exceptional. In a world with advances in imaging technology the early detection of an abdominal pregnancy should be a feasible objective .A case report of advanced abdominal pregnancy ending up in an alive male baby is presented.